Life course similarities on social networking sites. (December 2016) - Dávid-Barrett, T.; Behncke Izquierdo, I.; Carney, J.; Nowak, K.; Launay, J.; Rotkirch, A.
Abstract: Dyadic social relations are known to exhibit homophily – attraction and bonding between similar individuals – and recent studies have detected homophily also on the social network level. Here, we investigate whether social media networks exhibit signs of homophily with regards to life stages. Using a large and global database (N = 111, 863) of social media profile pictures, we investigate proportions of picture types in an individual's social network. Typical stages of young adulthood include peer group formation, mate searching, union formation, and parenting. We studied to what extent different association categories with pictures of one or several individuals correlated with each other. Results showed that users with a profile picture of a single individual were more likely to have other profile pictures of single individuals of the opposite sex, but not of the same sex, in their social media network. Profile pictures of heterosexual couples were more likely to appear with other heterosexual couple pictures, and profiles with baby pictures were strongly associated with the frequency of other baby pictures within the same network; both of these types were negatively associated with the frequency of pictures of singles. Pictures of two females together were positively linked with the largest number of other association types. The results probably reflect both selection and contagion effects. We conclude that contemporary social media networks appear to exhibit homophily in displays related to mate searching, pair bonds, and the transition to parenthood.